Perancangan Tata Letak Fasilitas dengan Menggunakan Metode Line Balancing untuk Meningkatkan Efisiensi Produksi Home Industry Pembuatan Gitar - Pras, Adi; Purwati, Sri; Nugraheni, Diyah Dwi (UNIVERSITAS ISLAM SYEKH YUSUF TANGERANG, 2025)
The home guitar manufacturing industry has emerged as one of the leading sectors in the Baki District, Sukoharjo Regency. This home industry specializes in producing acoustic guitars through a buy-to-order system. One of the challenges faced by the guitar manufacturing home industry is the inefficient layout of the utilized facilities, as the production process for each guitar component takes place in different locations – specifically, four distinct sites for four workstations. Therefore, there is a need for integrative decision-making related to production processes, workflow, employee positions, and the layout of production machinery. Line Balancing is a method employed to optimize the efficiency of the production facility layout. namely Workstation 1 (body molding process), Workstation 2 (body assembly and sanding process), and Workstation 3 (painting and finishing process). The reorganization of these work elements aims to achieve better efficiency and workflow balance. Furthermore, the research results demonstrate that utilizing a work cycle of 28.57 minutes yields an efficiency rate of 99.17% and an effectiveness rate of 100%. Hence, the implementation of a 28.57-minute work cycle is considered a more efficient option, with a positive impact on workflow balance.